Pemberdayaan Santri melalui Pelatihan Kaligrafi dan Pemasaran Kreatif di Pesantren: Membangun Ekonomi Digital Berbasis Budaya Islam - Zaini Miftah; Ahmad Muthi'Uddin; Nur Kholis Majid (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
This community service activity aims to empower students at the Al-Fattah Islamic Boarding School in Lamongan through Arabic calligraphy training combined with creative marketing practices. This initiative is designed to improve the students' artistic skills and entrepreneurial awareness. The methods used include determining the goals and objectives of the extension, preparing training materials, implementing the training, evaluating and providing feedback, and providing ongoing mentoring. The results of this activity have a positive impact on improving the quality of work, understanding marketing, and the students' enthusiasm in developing calligraphy-based businesses. In addition, this program also contributes to building self-confidence, creativity, and economic independence within the Islamic boarding school environment, as a step towards the sustainability of the creative industry based on religious values.